Utilizing crowd-sourced bathymetry for post disaster analysis – A case study - Solomon, Shaul; Yoselevich, Uri; Tunik, Ariel (The International Hydrographic Review, 2025)
This paper discusses two main use cases where DockTech’s Crowd-Sourced Bathymetry (CSB) was utilized to aid the port of Rio Grande (Brazil) during severe flooding. (1) Daily Data Collection and Analysis: DockTech implemented a system to collect daily bathymetric information from tugboats operating in the port. By comparing this data to established reference points, the port was able to estimate daily changes in the underwater environment, enabling timely and informed decision-making. (2) Emergency Monitoring Operations: In the absence of accessible traditional surveys, the port commissioned two tugboats, equipped with CSB equipment, to conduct survey operations in the entrance channel. The data collected through these efforts allowed the port to make informed adjustments to draft restrictions by an extra 30 cm, ensuring safe passage for vessels despite the challenging conditions. Key findings from these efforts include the identification of channel edges with deposition, the detection of shallow regions in the entrance channel, and the facilitation of lifting draft restrictions from 11.9 m to 12.2 m. These outcomes demonstrate the practical applications and advantages of CSB-based technologies in responding to natural disasters, providing critical support to port operations under challenging conditions.